Effect of aramid core-spun yarn on impact resistance of aramid/epoxy composite - Miao, Yajing; Ni, Jiahuan; Zhu, Kai; Liu, Yizhou; Chang, Yu; Gong, Zixin; Yang, Dan; Zhang, Xin (Frontiers in Materials, 2023)
The surface of aramid filament is smooth, which is a great defect for impact resistance and composite molding of aramid/epoxy composite. In this study, a new type of yarn –aramid core-spun yarn is introduced to the fabrication of composite materials. It increases the friction among yarns and optimizes the performance of yarns. To verify the improvement of yarn in the composite material, the first layer and the fourth layer are replaced by core-spun yarns in a four-layer composite configuration. The energy absorption, and the damage of the impacted surface and the back surface are evaluated through the drop weight impact test. The yarn pull-out test can reflect the internal friction of fabric. The results show that the average energy absorption of new yarn in the first layer is 10 J•cm 2 /g more than that in the fourth layer at a 90°/45°/-45°/0°24 configuration after the normalization, but the conclusion is contrary when the structure is -45°/0°/90°/45°. Under the structure of 90°/45°/-45°/0°, the damaged area of the fabric is larger when the aramid core-spun yarn is laid on the first layer, while a contrary result can be found for the structure of -45°/0°/90°/45°. The fundamental research will provide design ideas and supports for aramid composite.